Strategic Solutions: How Mathematics Reshapes Industrial Landscapes - T.R. Vijayaram; N Ramya (International Journal of Industrial and Product Design Engineering, 2024)
One of the earliest and most fundamental fields of the physical sciences is mathematics. It has a significant impact on industrial enterprises' bottom lines and enhances their performance in the current data-driven market. One subfield of applied mathematics is industrial mathematics. It concentrates on issues that arise in the industry and seeks answers that are pertinent to the sector. The use of mathematical models and techniques to diverse industry difficulties has garnered a lot of interest lately. Statistics, trigonometry, dynamics, optimization, and mathematical modeling approaches are all used in industrial algebra. Applied mathematics is a subfield of algebra that focuses only on practical applications and includes the study of computational and physical sciences. It is heavily utilized in computer science and engineering and is based on numerical techniques. A relatively recent area of mathematics research called "industrial mathematics" focuses on using mathematical modeling to solve practical issues in the real world, providing the groundwork for the creation of new technologies. It includes both pure and practical mathematical modeling, including dynamics, discrete mathematics such as calculus, likelihood, statistics, and partial differential equations. To put it another way, it will combine and restructure applied and pure mathematics into a dynamic form that can effectively meet the demands of diverse industries. In contrast to other sciences, industrial mathematics focuses on industry problems and seeks to identify pertinent solutions, including the most economical and efficient approach to address the issue. The need for mathematical skills is growing daily due to the intricate and advanced nature of today's industries. The newest computer techniques, computer graphics, system reliability software testing and verification, or databases can all be used to develop solutions through mathematical models. The function and applications of algebra in industry are covered in this summary study.
Keywords: Database; Industrial mathematics; Mexican manufacturing; industry; statistics